To find the equation of the parabola that fits the points given in the table, we can use the standard form of a quadratic equation:
\[ y = ax^2 + bx + c \]
The points provided are:
- (-1, -6)
- (1, 14)
- (3, -6)
- (5, -6)
Let's assign the coordinates for these points:
- \((-1, -6) \rightarrow (-1, -6)\)
- \((1, 14) \rightarrow (1, 14)\)
- \((3, -6) \rightarrow (3, -6)\)
- \((5, -6) \rightarrow (5, -6)\)
Since we have four points, we can use three of them to set up a system of equations.
Using points 1, 2, and 3:
-
For \((-1, -6)\): \[ -6 = a(-1)^2 + b(-1) + c \implies -6 = a - b + c \quad \text{(Equation 1)} \]
-
For \((1, 14)\): \[ 14 = a(1)^2 + b(1) + c \implies 14 = a + b + c \quad \text{(Equation 2)} \]
-
For \((3, -6)\): \[ -6 = a(3)^2 + b(3) + c \implies -6 = 9a + 3b + c \quad \text{(Equation 3)} \]
Now we'll write these equations in matrix form and solve for \(a\), \(b\), and \(c\).
Step 1: Set Up the System
From our equations:
- Equation 1: \(a - b + c = -6\)
- Equation 2: \(a + b + c = 14\)
- Equation 3: \(9a + 3b + c = -6\)
Step 2: Subtract Equations
Let's eliminate \(c\) by subtracting Equation 1 from Equation 2 and then Equation 2 from Equation 3:
From Equation 1 and Equation 2: \[ (a + b + c) - (a - b + c) = 14 - (-6) \ 2b = 20 \implies b = 10 \]
From Equation 2 and Equation 3: \[ (9a + 3b + c) - (a + b + c) = -6 - 14 \ 8a + 2b = -20 \implies 8a + 2(10) = -20 \ 8a + 20 = -20 \ 8a = -40 \implies a = -5 \]
Step 3: Find \(c\)
Now substitute \(a\) and \(b\) back into Equation 1 to find \(c\): \[ -5 - 10 + c = -6 \ c = -6 + 15 = 9 \]
Conclusion
Now we have the values:
- \(a = -5\)
- \(b = 10\)
- \(c = 9\)
Thus, the equation of the parabola is: \[ y = -5x^2 + 10x + 9 \]
This is your final answer. You can enter it as:
\[ y = -5x^2 + 10x + 9 \]